2019
DOI: 10.21203/rs.2.14490/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic and evolutionary features of two AHPND positive Vibrio parahaemolyticus strains isolated from shrimp (Penaeus monodon) of south-west Bangladesh

Abstract: Background Due to its rapid lethal effect in the early stage of shrimp, acute hepatopancreatic necrosis disease (AHPND) causing great economic losses, since it first outbreak in southeast China in 2009. Vibrio parahaemolyticus , carrying the pir A and pir B toxin genes is known to cause AHPND in shrimp. The overall objective of this study was to sequence whole genome of AHPND positive V. parahaemolyticus strains isolated from shrimp ( Peneaus monodon ) of south-west region of Bangladesh in 2016 and 2017 and ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…In the genome data, no TDH or TRH gene was identified, but a gene encoding TLH was identified. This result is consistent with the results reported by other scholars (Ahmmed et al., 2019). This finding indicates that seafood is rarely toxic to humans when heated adequately.…”
Section: Discussionsupporting
confidence: 94%
“…In the genome data, no TDH or TRH gene was identified, but a gene encoding TLH was identified. This result is consistent with the results reported by other scholars (Ahmmed et al., 2019). This finding indicates that seafood is rarely toxic to humans when heated adequately.…”
Section: Discussionsupporting
confidence: 94%
“…Other studies also suggested that genes involved in chemotaxis and motility, Type III secretion system‐1 (T3SS‐1) and its secreted effectors, thermolabile haemolysin were potentially contributing to the shrimp infection (Ahmmed et al . 2019; Shaheer et al . 2019; Lu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Shrimp is also prone to various disease outbreaks like WSSV, AHPND and various pathogenic organisms as the farmers were not able to maintain their farms properly during this pandemic [30]. Therefore, due to COVID-19 the Shrimp farmers harvested the diseased Shrimp and sold at lower price that ultimately affect their income status.…”
Section: Discussionmentioning
confidence: 99%